Influence of Maternal Dental Anxiety and the Child's DMFT Score - Kabli, Kholoud. (Tufts University. Tisch Library., 2019)
ABSTRACT Aim and Hypothesis: To determine the association between Maternal Dental Anxiety and a Child's Decayed, Missing, Filled Teeth (DMFT). Materials and Methods: A cross sectional study, where each mother was asked to complete a 19-question survey consisting of the Modified Dental Anxiety Scale (MDAS) (English, Spanish and Chinese version) questionnaire. Mother's educational level, location (urban or rural and suburban) family income status, mother's age, mother's pervious dental experience, ethnicity and race (of mother and child), child's gender, rank of child, child's previous dental experience, dental insurance was recorded via a tablet through Qualtrics. The survey was used to assess the maternal dental anxiety. Children's DMFT, Diet Score and the Caries-risk Assessment Tool (CAT) Score were obtained from patient's Axium record during the dental visit. Data was analyzed using independent samples t-test, Chi-square, Wilcoxon Signed Rank test and Shapiro-Wilk test. Results: With a sample size of 98, 51 mothers reported to be anxious. There was a positive correlation between child's DMFT score (p= 0.005), child's diet score (p=0.014), child's birth order (p=0.051), reason of dental visit (p=0.050) and maternal dental anxiety. Mother's education (p=0.52) and previous dental experience (p=0.059) had no effect on mother's anxiety level. When comparing Child's DMFT score with different variables, there was a statistically significant difference with child's age (p=0.03), child's ethnicity (p=0.005) and mother's ethnicity(p=0.007). Conclusion: There is a strong positive association between maternal dental anxiety and child's DMFT score. In addition, child's diet score was correlated to mother's anxiety showing that children with anxious mothers had poor diet habits.; Thesis (M.S.)--Tufts University, 2019.; Submitted to the Dept. of Pediatric Dentistry.; Advisor: Cheen Loo.; Committee: Sarah Pangi, Mohammad Hassan, and Gerald Swee.; Keyword: Dentistry.